2016
DOI: 10.25115/ecp.v9i18.997
|View full text |Cite
|
Sign up to set email alerts
|

El modelo de responsabilidad personal y social a través del deporte como propuesta metodológica para la educación en valores en adolescentes

Abstract: RESUMEN:En este estudio se presenta el Modelo de Responsabilidad Personal y Social, desarrollado por Donald Hellison, como herramienta para la educación en valores y la mejora de la convivencia escolar a través de las clases de educación física y el deporte escolar. Se describe la metodología y las características del mismo, distinguiendo los cinco niveles de los que se compone (respeto por los demás, participación y esfuerzo, autonomía personal, ayuda a los demás y liderazgo y transferencia fuera del contexto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
(12 reference statements)
1
4
0
3
Order By: Relevance
“…Likewise, Escartí, Gutiérrez, and Pascual (2011) showed that encouraging prosocial behaviour, empa thy and the perception of efficacy positively predict students' personal and social responsibility. Similarly, the study by SánchezAlcaraz et al (2016) confirmed improvements in students' quality of life.…”
Section: Discussionsupporting
confidence: 59%
“…Likewise, Escartí, Gutiérrez, and Pascual (2011) showed that encouraging prosocial behaviour, empa thy and the perception of efficacy positively predict students' personal and social responsibility. Similarly, the study by SánchezAlcaraz et al (2016) confirmed improvements in students' quality of life.…”
Section: Discussionsupporting
confidence: 59%
“…The functioning of the PE sessions should follow this structural pattern. In this way, learners are immersed in a routine process that will lead to faster progress in a work format they are familiar with and used to [39].…”
Section: Daily Program Formatmentioning
confidence: 99%
“…Thus, the Personal and Social Responsibility Model (TPSR) (Hellison, 2011) is one of the more effective teaching models in education of values through sport that emerged to help adolescents with social exclusion risk because it aims to help students experience success through situations that promote their personal and social skills and values development, as much in sport as in their daily life (Escartí et al, 2005;Sánchez-Alcaraz, Gómez-Mármol, Valero, De la Cruz, & Díaz, 2016). To acquire and learn the behaviors related with MORENO-MURCIA, J.A., LOCHBAUM, M.R 6…”
Section: Introductionmentioning
confidence: 99%